Pengembangan Lms Menggunakan Project Based Learning Untuk Pembelajaran Pemrograman Berorientasi Obyek Siswa Kelas X Rpl Smk - Sefni Marcella Pratiwi; Ekohariadi (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Object-Oriented Programming (OOP) instruction at SMK Negeri 2 Mojokerto is still dominated by conventional teaching methods, resulting in suboptimal student participation and learning media that do not adequately support interactive learning. This study aims to develop a Moodle-based Learning Management System (LMS) using the Project Based Learning (PjBL) model and determine its feasibility as well as differences in students' learning outcomes. The research employed the Research and Development (R&D) method using the ADDIE model. The participants consisted of 70 tenth-grade Software Engineering (RPL) students divided into an experimental class and a control class using a nonequivalent control group design. Data were collected through expert validation sheets and learning outcome tests, then analyzed using normality, homogeneity, Mann-Whitney U, and Independent Sample t-tests. The LMS achieved high validity, with validation scores ranging from 93% to 96%. The experimental class obtained higher cognitive (88.43 vs. 78.57) and psychomotor (94.29 vs. 84.29) scores than the control class, with significant differences (p < 0.05). Therefore, the Moodle-based LMS using the PjBL model is considered valid and demonstrates significant differences in learning outcomes compared with conventional instruction.